Structural and Dynamic Features of the MutT Protein in the Recognition of Nucleotides with the Mutagenic 8-Oxoguanine Base - Nakamura, Teruya (American Society for Biochemistry and Molecular Biology, 2010)
Escherichia coli MutT hydrolyzes 8-oxo-dGTP to 8-oxo-dGMP, an event that can prevent the misincorporation of 8-oxoguanine opposite adenine in DNA. Of the several enzymes that recognize 8-oxoguanine, MutT exhibits high substrate specificity for 8-oxoguanine nucleotides; however, the structural basis for this specificity is unknown. The crystal structures of MutT in the apo and holo forms and in the binary and ternary forms complexed with the product 8-oxo-dGMP and 8-oxo-dGMP plus Mn(2+), respectively, were determined. MutT strictly recognizes the overall conformation of 8-oxo-dGMP through a number of hydrogen bonds. This recognition mode revealed that 8-oxoguanine nucleotides are discriminated from guanine nucleotides by not only the hydrogen bond between the N7-H and Oδ (N119) atoms but also by the syn glycosidic conformation that 8-oxoguanine nucleotides prefer. Nevertheless, these discrimination factors cannot by themselves explain the roughly 34,000-fold difference between the affinity of MutT for 8-oxo-dGMP and dGMP. When the binary complex of MutT with 8-oxo-dGMP is compared with the ligand-free form, ordering and considerable movement of the flexible loops surrounding 8-oxo-dGMP in the binary complex are observed. These results indicate that MutT specifically recognizes 8-oxoguanine nucleotides by the ligand-induced conformational change.